Preparing future primary school teachers to organize a group form of student learning (Pedagogy of Higher and Secondary Education, 2012)
Kravtsova A. O. Preparing future primary school teachers to organize a group form of student learning.The question of the future teacher training of primary schools for the organization of group studying of pupils, forms and types of group working according to different criteria are under consideration in this article.
Keywords: form of group working; organization of group form of working; models of cooperation in groups; professional teacher training